Real-life treatment persistence and treatment outcomes of Finnish patients with inflammatory bowel disease receiving vedolizumab as first-line biological treatment - Ylisaukko-oja, Tero; af Björkesten, Clas-Göran; Eberl, Anja; Nuutinen, Heikki; Jussila, Airi; Molander, Pauliina; Koskela, Ritva; Blomster, Timo; Pajala, Markku; Ilus, Tuire; Haiko, Paula; Kovac, Bianca; et al. (Elsevier, 2025)
Purpose: To analyze treatment persistence and treatment outcomes of vedolizumab as first-line biological treatment in Crohn's disease (CD) and ulcerative colitis (UC) patients in a Finnish real-world setting.
Methods: Observational, retrospective, multi-center chart review study that included adult CD and UC patients initiating vedolizumab as first-line biological treatment between 2014 and 2020.
Results: The cohort consisted of 54 CD and 69 UC patients. At month 12, treatment persistence was 84.9 % in CD and 64.7 % in UC. Most vedolizumab discontinuations (CD, n = 11; UC, n = 26) were due to inefficacy. Discontinuations due to adverse events were rare (n < 5). Efficacy improvements were observed in treatment persistent patients at 12 months vs. baseline in the Harvey-Bradshaw Index (CD, 1.8 vs. 3.9, p = 0.001), Partial Mayo Score (UC, 1.0 vs. 4.9, p < 0.001), Physician's Global Assessment (CD, 0.9 vs. 1.8, p < 0.001; UC, 0.4 vs. 2.1, p < 0.001), along with positive endoscopic and biochemical outcomes. Clinical remission was 90.9 % vs. 63.0 % for CD, and 81.6 % vs. 12.3 % for UC, while corticosteroid use was 15.9 % vs. 53.7 % for CD, and 14.6 % vs. 92.8 % for UC at 12 months and baseline, respectively.
Conclusion: Vedolizumab was associated with improvements in efficacy, endoscopic activity, biochemical parameters, and decreased corticosteroid burden when used as a first-line biological treatment.